The Ethanol Extract of Croton Seed Inhibits the Oral Pathogen, Streptococcus mutans - Kim, Ji-Hee; Jung, Sam-Sung; Kang, Chung-Hoon; You, Yong-Ouk; Kim, Kang-Ju (International journal of oral biology, 2018)
It is noted that Streptococcus mutans (S. mutans) triggers dental caries establishment by two major factors: the synthesis of organic acids, which demineralize dental enamel, and the synthesis of glucans, which mediate the attachment of bacteria to the tooth surface. Therefore, it is noted that the development of a more effective, substantial and safe preventive agent that works against dental caries and periodontal disease is required at this time. For this reason, the present study was designed to investigate the effect of croton seed ethanol extracts on the growth, acid production, adhesion, and insoluble glucan synthesis of S. mutans. In this case, the ethanol extract of croton seed showed concentration dependent inhibitory activity against the growth, acid production and adhesion of S. mutans. Especially, it is important to note that it has produced significant inhibition at the concentration of 0.1 and 0.2 mg/ml as compared to the control group. Moreover, these results suggest that the application of croton seed extract may be considered to be a useful method for the prevention of dental caries.